The amoebicidal activity of Chaerophyllum macropodum extract on Acanthamoeba genotype T4 in vitro - Tooran Nayeri; Farahnaz Bineshian; Fariba Khoshzaban; Abdolhossein Dalimi Asl; Mohammad Saaid Dayer; Fatemeh Ghaffarifar (مجله علمی دانشگاه علوم پزشکی کردستان, 2022)
Background and Aim: Acanthamoeba is an opportunistic pathogen that may cause fatal granulomatous encephalitis and ocular keratitis in humans and animals. Increasing number of contact lens wearers can lead to increased frequency of amoebic keratitis and due to lack of effective drugs treatment of this disease is difficult. This study aimed to investigate the effect of ethanolic extract of Chaerophyllum macropodum on Acanthamoeba genotype T4. Materials and Methods: In this experimental study, samples taken from the patients with keratitis were cultured on 1.5% non-nutrient agar medium. Different concentrations of the ethanolic extract (1.25, 2.5, 5, 10 mg/ml) were tested three times (24, 48, and 72 h) on trophozoites and cysts of Acanthamoeba in vitro. The number of live and dead parasites were counted by using trypan blue staining and neobar lam. Also, the percentage of cysts apoptosis was assessed by flow cytometry. Results: In the presence of 10 mg/ml ethanolic extract in the culture medium, the percentages of live trophozoites after 24, 48, and 72 h were 53.6, 15.11, and 0 percent, respectively. In the case of cysts, after 24, 48, and 72 h, 65.31, 43.31, and 0 percent of the cysts were alive, respectively. The results of flow cytometry showed that the apoptosis rate was 0.09% in the sample treated with extract after 72 h. Conclusion: Ethanolic extract of Chirophyllum macropodium can be a promising candidate for the development of anti-Acanthamoeba drugs due to its high toxic effects on the cysts. However, since the crude extract of Chaerophyllum macropodum was used in this study, further investigations are needed to find the effective fractions of the plant and determine their mechanisms of action. It can also be tested in vivo or even against other parasites